RETRACTED: Spectroscopic and molecular modeling studies of binding interaction between the new complex of yttrium and 1,10-phenanthroline derivatives with DNA and BSA - Khorshidi, Mahsa; Asadpour, Saeid; Aramesh-Boroujeni, Zahra; Kooravand, Masoumeh; Mobini Dehkordi, Maryam (Frontiers in Chemistry, 2023)
In this study, the 4,9 diazafluoren-9-one ligand and [Y(Daf)2Cl3.OH2] complex were synthesized. The interaction of this complex with DNA and bovine serum albumin (BSA) was investigated by UV-vis and fluorescence spectroscopy. The molecular docking method was used to confirm the experimental results, investigate the type of interaction, and determine the binding site. The binding constant and Stern–Volmer constant were calculated using spectroscopy techniques. The binding constant of the Y-complex with DNA and BSA obtained using the UV-vis technique was 1.61 × 105 M−1 and 0.49 × 105 M−1, while that obtained using the fluorescence method was 3.39 × 105 M−1 and 3.63 × 105 M−1, respectively. The results of experimental and theoretical data showed that the interaction between the yttrium complex and DNA and BSA is driven by the hydrogen bond and van der Waals interaction, respectively. The yttrium complex communicates with DNA via the groove interaction. This complex has high binding energy with bovine serum albumin. In addition, the molecular docking results showed that the complex binds to the IIA subdomain of BSA (site I). Finally, anticancer activity of the yttrium complex was studied on MCF-7 and A549 cell lines by using the MTT method. The IC50 values obtained showed that the yttrium complex possesses anticancer activity.